Next-Generation Sequencing in Post-mortem Genetic Testing of Young Sudden Cardiac Death Cases - Lahrouchi, Najim; Behr, Elijah R.; Bezzina, Connie R. (Frontiers in Cardiovascular Medicine, 2016)
Sudden cardiac death (SCD) in the young (<40 years) occurs in the setting of a variety of rare inherited cardiac disorders and is a disastrous event for family members. Establishing the cause of SCD is important as it permits the pre-symptomatic identification of relatives at risk of SCD. Sudden arrhythmic death syndrome (SADS) is defined as SCD in the setting of negative autopsy findings and toxicological analysis. In such cases reaching a diagnosis is even more challenging and post mortem genetic testing can crucially contribute to the identification of the underlying cause of death. In this review, we will discuss the current achievements of ‘the molecular autopsy’ in young SADS cases and provide an overview of key challenges in assessing pathogenicity (i.e. causality) of genetic variants identified through next-generation sequencing.